D-C ACO-OFDM and DCO-OFDM for passive optical network: Performance comparison in IM/DD fiber link - SANYA, MAX FREJUS O.; AUPETIT-BERTHELEMOT, Christelle; DJOGBE, LÉOPOLD; VIANOU, Antoine (My University, 2014)
We present a comparative study of DiversityCombined Asymmetrically Clipped Optical OFDM (D-C ACOOFDM) and DC-biased Optical OFDM (DCO-OFDM) techniques in 17Gbps intensity modulated and direct detected (IM/DD) fiber link of passive optical network (PON). From simulation results obtained with realistic components parameters, we find that D-C ACO-OFDM offers an improved demodulation than DCO-OFDM. Using 4QAM format and split ratio of 1x32, D-C ACO-OFDM is showed to reach 45.3km distance which is almost the double distance transmission of DCO-OFDM with the same modulation order. We also show at BER of 10-3, that 20km transmission distance can be reached at 24Gbps 4QAM D-C ACO-OFDM data rate and then D-C ACOOFDM is a suitable efficient cost-effective solution for GPON deployment with benefit of use of low-cost laser bandwidth in comparison with DCO-OFDM. At the same BER performance, in comparison with D-C ACO-OFDM at high bit rates transmission, DCO-OFDM promises to deliver higher throughput. The Bit Error Rate (BER) performance value is fixed to 10-3 (limit value when Forward Error Codes are used).
Keywords: Optical OFDM; IM/DD; PON; BER.